A chronicle of the 17-alpha hydroxyprogesterone caproate story to prevent recurrent preterm birth - Nelson, David B.; McIntire, Donald D.; Leveno, Kenneth J. (American journal of obstetrics and gynecology, 2021)
Preterm birth is a substantial public health concern. In 2019, the US preterm birth rate was 10.23%, which is the fifth straight year of increase in this rate. Moreover, preterm birth accounts for approximately 1 in 6 infant deaths, and surviving children often suffer developmental delay or long-term neurologic impairment. Although the burden of preterm birth is clear, identifying strategies to reduce preterm birth has been challenging. On October 29, 2019, a US Food and Drug Administration advisory committee voted 9 vs 7 to withdraw interim accelerated approval of 17-alpha hydroxyprogesterone caproate for preventing recurrent preterm birth because the called for a confirmatory trial, known as the Prevention of Preterm Birth in Women With a Previous Singleton Spontaneous Preterm Delivery trial, was not confirmatory. The Prevention of Preterm Birth in Women With a Previous Singleton Spontaneous Preterm Delivery trial included subjects enrolled in the United States and Canada to ensure that at least 10% of patients would be from North America; however, this trial took 9 years to complete and did not demonstrate significant treatment effects in the 2 primary outcomes of interest. Delivery before 35 weeks’ gestation occurred in 122 of 1130 women (11%) given 17-alpha hydroxyprogesterone caproate compared with 66 of 578 women (11.5%) given placebo (relative risk, 0.95; 95% confidence interval, 0.71–1.26; P=.72). Similarly, the coprimary outcome neonatal composite index occurred in 61 of 1093 women (5.6%) given 17-alpha hydroxyprogesterone caproate compared with 28 of 559 women (5.0%) given placebo (relative risk, 1.12; 95% confidence interval, 0.68–1.61; P=.73). There was also a lack of efficacy for 17-alpha hydroxyprogesterone caproate treatment in the analysis of a variety of secondary outcomes. Like the Maternal-Fetal Medicine Units Network trial, the Prevention of Preterm Birth in Women With a Previous Singleton Spontaneous Preterm Delivery trial was also flawed. Importantly, the Maternal-Fetal Medicine Unit Network trial was the sole justification for treating women in the United States with 17-alpha hydroxyprogesterone caproate for nearly 2 decades. Currently, despite more than half a century, 17-alpha hydroxyprogesterone caproate still has not been found to be clearly effective. In this context, how does the advising physician dependent on scientific evidence advise a patient that 17-alpha hydroxyprogesterone caproate is effective when the evidence to support this advice has repeatedly been found to be inadequate? This clinical opinion is a critical appraisal of the 2 randomized trials examining the efficacy of 17-alpha hydroxyprogesterone caproate to prevent recurrent preterm birth and a chronicle of events in the regulatory process of drug approval to help answer this question. With this examination, these events illustrate the complexity of pharmaceutical regulations in the era of accelerated Food and Drug Administration approval and characterize the financial impact and influence in medicine. In this report, we also emphasize the value of observational studies in contemporary practice and identify other examples in medicine where accelerated Food and Drug Administration approval has been withdrawn. Importantly, the themes of the 17-alpha hydroxyprogesterone caproate story are not limited to obstetrics. It can also serve as a microcosm of issues within the US healthcare system, which ultimately contributes to the high cost of healthcare. In our opinion, the answer to the question is clear—the facts speak for themselves—and we believe 17-alpha hydroxyprogesterone caproate should not be endorsed for use to prevent recurrent preterm birth in the United States.